Exactitude, déterminants, effets et représentations de l’auto-évaluation chez des étudiants de première année universitaire - Valérie Wathelet; Matthieu Dontaine; Xavier Massart; Philippe Parmentier; Sandrine Vieillevoye; Marc Romainville (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
Within the context of an early and formative evaluation framework assessing prerequisites when entering university, first-year students were asked to practice self-assessment by estimating their degree of mastery of each assessed prerequisite on a three-level scale specified beforehand. With a view to a « sustainable » feedback, self-assessment has been introduced within this framework, since it represents a major step in a process aiming at developing student autonomy, which is essential to succeed in higher education. To start this self-assessment process, students had to take a so-called « Passport » and make a self-diagnosis. The latter is intended to bring students to enter a regulation process through their taking part to capacity-building activities. In this paper, we will first study the accuracy level of student self-assessment behaviour. Factors associated to this behaviour will be then analyzed, taking special attention to students’ gender (male/female), their real degree of mastery of prerequisites, as well as their taking part to capacity-building activities. Finally, we will analyze how students perceive the self-assessment activity itself. The article ends with a discussion on the limits of this research and some proposals of educational implications.